Cultivo de morango em ambiente tipo telado, sob manejos diferenciados de irrigação e de fertilização orgânica, nas condições climáticas de Fortaleza, Ceará - Lima, Francisco Aldiel (2014)
The fruit of the strawberry (Fragaria x anamassa Duch.) Is enjoyed all over the world, with planting accomplished in several regions, a fact that occurs the existence of cultivars adapted to different climates. But in the Northeast there is a big challenge for producers and researchers, mainly due to high temperatures and evapotranspiration and low rainfall. Another challenge is the search for a less dependent on mineral inputs agriculture. Biofertilizers are presented as an important tool for crop production, being generated from natural product obtained from the fermentation of organic materials. In consequence, the aim of this study was to evaluate the effects of irrigation and levels of bovine biofertilizer anaerobic fermentation under protected environment of the screenhouse type, in the climatic conditions in Fortaleza, Ceará. For this, the experiment was conducted in weather station at the Federal University of Ceará, Fortaleza, from August to December 2012, protected under the greenhouse type environment. Experimental design was a randomized complete block in a split-plot design in that the irrigation was applied through drip (equivalent to 33.3, 66.6, 100, 133.3, 166.6% of class A evaporation measured in tank, ECA), constituted the main plots. The four levels of cattle biofertilizer (125, 250, 375 and 500 ml plant-¹ week-¹) were the subplots with four replications. Were evaluated gas exchange (photosynthesis, stomatal conductance, transpiration, and internal CO2 concentration; at 40 and 110 DAT), the biomass (dry matter of the roots, shoot and total), the variables of harvest (diameter, length, number,average fruit weight and yield) and postharvest (total soluble solid, pH , titratable acidity and soluble solid ratio / acidity). The dose of 375 mL plant-¹ week-¹ is presented as the best dosage for strawberry culture in Ceará. The functions generated for most variables depending on irrigation were quadratic polynomial, with the best irrigation depths near in the 100% of ECA. The irrigation depths equivalent to 126.92% of ECA and bovine biofertilizer dose of 375 mL plant-¹ week-¹, provides further development of biomass. It is recommended for maximum production a irrigation depths equivalent to 101.35% of ECA and a bovine biofertilizer dose of 375 mL plant-¹ week-¹.